Pragmatic Analysis of Expressive Speech Acts in the Radio Drama Tutur Tinular-Series 010 Episode 1: Rainbow Above Kurawan - Azizah, Nur; Gustiasari, Dewi Rani; Latifah, Ade Yayang; Harisman, Tisna (Sean Institute, 2025)
This study aims to analyze expressive speech acts in the radio drama Tutur Tinular – Series 010, Episode 1: Pelangi di Atas Kurawan, using a pragmatic approach. Language functions not only as a means of communication but also as a medium for emotional and psychological expression that reflects the speaker’s inner state. Expressive speech acts, such as expressing gratitude, apologizing, praising, complaining, and criticizing, represent concrete manifestations of human emotions in language use. The research data were collected through listening and note-taking techniques and analyzed using a descriptive qualitative method based on the context of the utterances. The findings reveal fifteen instances of expressive speech acts, which are classified into several types, including apologizing, praising, self-blaming, complaining, expressing gratitude, threatening, and admiring. These expressive speech acts function to construct emotional atmospheres, deepen character development, and drive the narrative progression. Through these utterances, listeners are invited to experience emotional dynamics such as sadness, inner conflict, affection, tension, and empathy, which strengthen the dramatic value of the work. Moreover, the expressive speech acts convey Javanese moral and cultural values, including respect, politeness, and sincerity. This study confirms that expressive speech acts serve both aesthetic and pragmatic functions in oral literary works, as they contribute to depth of meaning, emotional richness, and cultural reflection within Indonesian society.